Rural opioid stewardship: Lessons learned from one community and the retirement of a pain management clinician - Holly Ann Russell; Jade Malcho; Michele Lawrence (Preventive Medicine Reports)
Objective: This commentary offers a perspective of a rural community's response to a dissolution of a pain management practice with an emphasis on how to avoid serious harm for patients on opioid therapy when continuity of chronic pain management care is interrupted. Methods: The ‘Ecosystem of Recovery”9 framework was utilized to explore the response of rural communities to pain management clinic closures that includes community engagement, incorporation of a multi-disciplinary team, clinician education and consultative support to deliver evidence-based care while triaging patient needs. This project was undertaken as a quality improvement initiative and did not meet the definition of research according to 45CFR46, the federal law dictating human subjects research in the US. Results: Community engagement resulted in a unified, multi-disciplinary team-based approach that supported existing medical infrastructure to transition patients seeking continuation of care. Emergency Departments linked patients to existing primary care offices, behavioral health and addiction medicine specialists based on patient presentation. Education and consultation efforts supported triage of their acute medical needs and linkage to appropriate level of care. Buprenorphine initiation to treat opioid withdrawal and harm reduction strategies for overdose prevention, including naloxone, were included at the core of the strategies. Conclusions: Implementation of clinician and patient support strategies are recommended when gaps in pain management treatment occur in resource-limited communities. We share our coordinated community-based approach for patients who are navigating this care transition, while educating and supporting clinicians how to evaluate and initiate treatment for opioid withdrawal and opioid use disorder.